2012
DOI: 10.1158/0008-5472.can-11-3157
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic ATM Methylation in Peripheral Blood DNA as a Biomarker of Breast Cancer Risk

Abstract: Few studies have evaluated the association between DNA methylation in white blood cells (WBC) and the risk of breast cancer. The evaluation of WBC DNA methylation as a biomarker of cancer risk is of particular importance as peripheral blood is often available in prospective cohorts and easier to obtain than tumor or normal tissues. Here, we used prediagnostic blood samples from three studies to analyze WBC DNA methylation of two ATM intragenic loci (ATMmvp2a and ATMmvp2b) and genome-wide DNA methylation in lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 44 publications
6
131
3
Order By: Relevance
“…Also, a higher ICC was observed in ATBC compared with the PLCO study. Although ICCs are rarely reported, in comparison to Liao et al 19 and a previous study of breast cancer, 21 the ICCs we report are comparatively higher. Strengths of this study include the high quality questionnaire data collected prior to cancer diagnosis, thus reducing the risk of recall bias.…”
Section: Discussioncontrasting
confidence: 81%
“…Also, a higher ICC was observed in ATBC compared with the PLCO study. Although ICCs are rarely reported, in comparison to Liao et al 19 and a previous study of breast cancer, 21 the ICCs we report are comparatively higher. Strengths of this study include the high quality questionnaire data collected prior to cancer diagnosis, thus reducing the risk of recall bias.…”
Section: Discussioncontrasting
confidence: 81%
“…Also, although methylation of LINE-1 repetitive elements has been shown to provide results that parallel those obtained from a direct measurement of genomic DNA methylation, 60 LINE-1 methylation has its limitations as a surrogate measure of genomic methylation and we are not certain that there is a definitive association between percent LINE-1 methylation (in WBCs or breast tissues) and breast cancer risk. 61 Another consideration is that our finding of a lack of a significant association between plasma or breast folate concentrations (which we recently showed are only modestly correlated [r D 0.21, P D 0.07] 52 ) and LINE-1 methylation could be due to measurement error, particularly for the breast folate assay which had a CV >10%. Finally, since there are no known clinically relevant cut-points/thresholds for LINE-1 methylation that are related to breast cancer risk, our findings of 1-4% differences in normal tissues (in association with some factors studied here) might be clinically relevant.…”
Section: Discussionmentioning
confidence: 84%
“…18,19 Nevertheless, the Illumina 27K Array is a limited genome-wide methylation screen. The reported BC-associated altered methylation loci of the ATM gene 16,17 and the differentially methylated DOK7 gene identified in the BC discordant identical twins 12 are not included in the Illumina 27K Array.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] A few aberrant methylation patterns in peripheral blood have also been reported in BC by candidate gene approaches. [16][17][18][19] Recently, Xu et al reported an extensive blood-based epigenome-wide association study of BC by Illumina 27K Methylation Array in a well-designed prospective sister study cohort, and demonstrated that the methylation profiling of blood are promising markers for BC detection and risk evaluation. 20 Hereby, we conducted an Infinium 27K Methylation Array on peripheral blood DNA in case-control study, and performed further independent validations by MassARRAY for BC-associated methylation variability.…”
mentioning
confidence: 99%